Forecasting, Structural Time Series Models, and the Kalman Filter - Harvey, A. C. (Cambridge; New York: Cambridge University Press, 1989)
This book provides a framework which includes behavioral econometric models as well as the simplest kinds of univariate time series models. It also emphasis is on the development of models which can be used in practice, and the way in which such models can be selected.
Includes bibliographical references (p. 529-542) and indexes.
asm; 12/03/2018
Loans
Keywords: Time-series analysis; Kalman Filtering